2022
DOI: 10.3390/children9020144
|View full text |Cite
|
Sign up to set email alerts
|

The Needs of Parents of Children Suffering from Cancer—Continuation of Research

Abstract: Background: Parents experience many healthcare needs when caring for their sick children. Research shows that parents of oncological children have a high level of unmet needs, including psychosocial, emotional, physical, informational, financial, educational, and spiritual needs. To date, little quantitative research has been carried out on the specific needs of parents of children with cancer, which creates uncertainty about what areas should be addressed in care. This study investigated the prevalence of unm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 51 publications
2
22
0
1
Order By: Relevance
“…This study was unique in evaluating the specific needs of families facing a single diagnosis, treated on the same treatment regimen, and whose initial informed consent conversations were based off the same source documents. Yet, participants in our study still had many unmet communication needs similar to those found in other studies of multiple pediatric malignancies, such as anticipatory guidance on treatment side effects, practical aspects of care, and psychosocial support 30,31 . Echoing other studies, even those who felt they received excellent information from their clinical teams still valued additional resources 31,32 .…”
Section: Discussionsupporting
confidence: 51%
“…This study was unique in evaluating the specific needs of families facing a single diagnosis, treated on the same treatment regimen, and whose initial informed consent conversations were based off the same source documents. Yet, participants in our study still had many unmet communication needs similar to those found in other studies of multiple pediatric malignancies, such as anticipatory guidance on treatment side effects, practical aspects of care, and psychosocial support 30,31 . Echoing other studies, even those who felt they received excellent information from their clinical teams still valued additional resources 31,32 .…”
Section: Discussionsupporting
confidence: 51%
“…In the results already evidenced previously by Fjose et al 6 , the division of roles, identification of the needs of each family member and the promotion of significant time had a stress-reducing effect in the family group of people with cancer. In a Polish study 33 , which addressed the needs of parents of children suffering from cancer, the author states that the greatest need of family members is for information. Therefore, dialogue with the family, whether individually or in a family unit, in addition to being essential, is the main strategy for including family members in the treatment and care of the individual 33 .…”
Section: Discussionmentioning
confidence: 99%
“…In a Polish study 33 , which addressed the needs of parents of children suffering from cancer, the author states that the greatest need of family members is for information. Therefore, dialogue with the family, whether individually or in a family unit, in addition to being essential, is the main strategy for including family members in the treatment and care of the individual 33 . Thus, studies are needed to better explain the approach to family dynamics as a form of support for caregivers, especially in relation to cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the parents’ speech content facilitates the gathering of information, allowing us to understand the situations experienced from their personal perspective [ 20 ]. Not only are the parents’ health and well-being affected by childhood cancer, but various areas of their daily functioning undergo important changes that affect the quality of the entire family’s life [ 21 , 22 ]. Having to reduce working hours to accompany the child during their treatment, economic difficulties, poor and sometimes almost non-existent relationships with friends, relationship problems, and scant attention paid to the rest of the family are among some of the most evident consequences [ 3 ].…”
Section: Introductionmentioning
confidence: 99%